Determination of selenium and copper in water and food by hierarchical dendritic nano-gold modified glassy carbon electrodes. Issue 13 (16th June 2021) - Wang, Haofan; Guo, Yin; Pan, Hongcheng
Abstract : Hierarchical dendritic gold nanostructured films were electrodeposited on a GCE at a potential of −0.6 V and used for square-wave anodic stripping voltammetry to determine nanomolar levels of Se and Cu in water and food. Abstract : The sensitive determination of selenium and copper is of importance for environmental monitoring and food safety. A stripping voltammetric determination of selenium and copper in water and selenium-rich foods was developed using hierarchical dendritic gold nanostructure (AuHD) modified glassy carbon electrodes (GCE). The AuHD thin films were electrodeposited potentiostatically onto the GCE from a solution containing 25 mM HAuCl4 and 0.1 M Na2 SO4 at −0.6 V for 20 min. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) studies showed that the electrodeposited gold thin film shows a nanoforest-like morphology with a thickness of about 30–40 μm and a hierarchical dendritic structure with primary-, secondary-, and higher-order branches. Se(iv ) and Cu(ii ) in a 0.1 M H2 SO4 solution were determined by square-wave anodic stripping voltammetry using the AuHDs/GCE as the working electrode. Prior to anodic stripping, Se(iv ) and Cu(ii ) were accumulated onto the working electrode surface at −0.2 V for 300 s. The stripping peak currents of Se(iv ) at 0.81 V and Cu(ii ) at 0.31 V were positively correlated with the concentrations of Se(iv ) and Cu(ii ) in a range of 50–700 nM. The limits of detection (3 σ ) for Se(iv ) and Cu(ii ) were 1.4 nM and 3.7 nM, respectively. The accuracy of the method was verified by analysing certified water standard reference materials, and the results showed that the method has good accuracy and high precision. The method was used to determine selenium and copper in tap water, selenium-rich rice and selenium-rich eggs. The results were compared with those obtained by using inductively coupled plasma-mass spectrometry (ICP-MS) and found to be consistent with those of ICP-MS. The proposed method had the advantages of simplicity, rapidity, good reproducibility, and high sensitivity and it can be used for the analysis of real samples.